Evidence of Returns to Schooling in Africa from Household Surveys: Monitoring and Restructuring the Market for Education - T. Paul Schultz (Yale University, Economic Growth Center, 2003)
Wage-differentials by education of men and women are examined from African household surveys to suggest private wage returns to schooling. It is commonly asserted that returns are highest at primary school levels and decrease at secondary and postsecondary levels, whereas private returns in six African countries are today highest at the secondary and post secondary levels, and rates are similar for women as for men. The large public subsidies for postsecondary education in Africa, therefore, are not needed to motivate students to enroll, and those who have in the past enrolled in these levels of education are disproportionately from the better-educated families. Higher education in Africa could be more efficient and more equitably distributed if the children of well-educated parents paid the public costs of their schooling, and these tuition revenues facilitated the expansion of higher education and financed fellowships for children of the poor and less educated parents.
Keywords: O15; O55; J31; J24; 330; Africa; Wage Returns to Schooling; Inequality; HIV/AIDS; Bildungsertrag; Einkommensverteilung; Bildungswesen; Bildungsfinanzierung; AIDS; Zentralafrika